2018
DOI: 10.15390/eb.2018.7034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Attitudes and Knowledge of Teachers Regarding the Concept of Radiation

Abstract: Bu çalışmanın amacı, öğretmenlerin radyasyon kavramına karşı tutum ve bilgi düzeyleri belirlemeye çalışmaktır. Araştırmanın örneklemini İç Anadolu'nun batısında yaklaşık ikiyüzellibin nüfuslu bir ilde ilkokul ve ortaokullarda farklı branşlarda çalışan 274 öğretmen oluşturmuştur. Çalışmada verilerin toplanması amacıyla kişisel bilgi anketi ve daha önce Torun, Yalçin ve Altun Yalçin (2011) tarafından geliştirilen radyasyon kavramına karşı tutum ölçeği kullanılmıştır. Elde edilen veriler SPSS 15 paket programına … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Medical Imaging Techniques students' level of knowledge about radiation was found to be better than other students. Yalçın et al also had investigated teachers 'attitudes towards radiation and found that science-technology and mathematics teachers' attitudes towards radiation concept were positively higher than other branch teachers (Yalçın, Karenoğulları, & Yalçın, 2018). It is thought that this situation depends on the received theoretical education and may be related to the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Medical Imaging Techniques students' level of knowledge about radiation was found to be better than other students. Yalçın et al also had investigated teachers 'attitudes towards radiation and found that science-technology and mathematics teachers' attitudes towards radiation concept were positively higher than other branch teachers (Yalçın, Karenoğulları, & Yalçın, 2018). It is thought that this situation depends on the received theoretical education and may be related to the curriculum.…”
Section: Discussionmentioning
confidence: 99%